Analisis Asupan Zat Gizi Makro, Vitamin C, Serat, dan Kadar Kolesterol Total pada Penderita Penyakit Jantung Koroner - Muzakar, Muzakar; Siti, Siti; Susyani, Susyani; Hendawati, Hendawati; Listrianah, Listrianah; Fadly, Fadly (Poltekkes Kemenkes Palembang, 2025)
Background: Background: Coronary heart disease (CHD) is the disruption of heart function due to lack of blood due to blockage of the coronary arteries which results in damage to the lining of the blood vessel walls (atherosclerosis). Objective: The purpose of this study is to know the analysis of intake of macronutrients, vitamin C, fiber, and total cholesterol levels in patients with coronary heart disease. This type of research is quantitative with a cross-sectional research design. Methods: This type of research is quantitative with a cross-sectional research design. This research was conducted from April to May 2023 at the Siti Fatimah Provincial Hospital. South Sumatra. The research sample was chosen by accidental sampling with a sample size of 60 respondents. Results: The results show that there is a significant relationship between excess intake of macronutrients and lack of consumption of fiber and vitamin C on increased total cholesterol levels. Conclusion: The conclusion from the results of statistical tests shows that there is a relationship between excess intake of macronutrients and lack of consumption.